1999
DOI: 10.1007/s002960050074
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in systemic lupus erythematosus

Abstract: A prospective echocardiographic and clinical study was performed on 84 Chinese patients with systemic lupus erythematosus (SLE) and 99 controls to investigate the prevalence and the mechanism of pulmonary hypertension (PH) in SLE. Comparison between Doppler estimation and catheterization measurement was made in 12 cases to validate the predictive method. Compared to normal subjects, lupus patients had significantly increased systolic pulmonary artery pressure (SPAP) (29.59 +/- 12.52 vs 19.64 +/- 5.82, P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 0 publications
1
60
1
3
Order By: Relevance
“…17-19 Some studies have suggested an imbalance between vasoconstrictors and vasodilators in SLE-APAH. 20 According to the present results, there might be difference in the principal mechanism of SLE-APAH according to SLE activity. In the present study, at a similar level of mPAP, lower SLEDAI was related to higher PVR, larger RV size, and worse RV longitudinal systolic function, which might indicate severer PAH in these patients.…”
Section: 02mentioning
confidence: 99%
“…17-19 Some studies have suggested an imbalance between vasoconstrictors and vasodilators in SLE-APAH. 20 According to the present results, there might be difference in the principal mechanism of SLE-APAH according to SLE activity. In the present study, at a similar level of mPAP, lower SLEDAI was related to higher PVR, larger RV size, and worse RV longitudinal systolic function, which might indicate severer PAH in these patients.…”
Section: 02mentioning
confidence: 99%
“…Bir araştırmaya göre PAH saptanan 105 SLE hastanın %90'ı kadın, ortalama yaş 33, PAH tanısından sonraki 2 yılda ölüm oranı %25-50 arasındadır (34). Çinlilerin yaptığı 84 hastalık çalışmada ekokardiyografi ile PAH %11 oranında gözlenmiştir, ancak SKK ile doğrulama yapılmamıştır (35). Ekokardiyografi sadece tarama amaçlı kullanılır, yüksek yalancı pozitiflik görülebilir.…”
Section: Introductionunclassified
“…interstitial lung disease) (9) . Pulmonary hypertension has been reported in 4%-14% of the patients with systemic lupus erythematosus (SLE) with an overall mortality rate of 25%-50% at two years from diagnosis of pulmonary hypertension (19)(20)(21)(22)(23)(24)(25) . Patients with mixed connective tissue disease (MCTD) have features of several connective tissue diseases including SLE, scleroderma, rheumatoid arthritis and polymyositis (26,27) .…”
Section: Introductionmentioning
confidence: 99%